SAT0104 The role of prolactin, as sex hormone, and its receptor involved in rheumatoid arthritis. (23rd January 2014) - Tang, M.W.; Gerlag, D.M.; Codullo, V.; Vieina de Sousa, E.C.; Reuwer, A.Q.; Twickler, M.; Landewé, R.B.; Tak, P.P.
Abstract : Background: Rheumatoid arthritis (RA) mainly affects women. Prolactin (PRL) is a sex hormone with immunomodulatory properties. High prolactin levels are associated with increased disease activity postpartum, and that the PRL-inhibitor bromocriptine improves disease activity of patients with RA. Hyperprolactinemia is observed in 6% of RA-patients, compared to 3% of healthy individuals. The prolactin receptor (PRLR), belonging to the family of cytokine receptors, has been described in atherosclerotic plaques, mainly on macrophages. Objectives: The objective of the study is to determine 1) the level of PRL in RA-patients related to treatment effect 2) PRLR expression in synovial tissue of RA, psoriatic arthritis (PsA) and osteoarthritis (OA) patients 3) the phenotype of the PRLR expressing cell. Methods: Serum prolactin levels were measured using immunofluorescent metric assay in patients with RA before TNF-α blockade (n=98). The expression of PRLR was determined in synovial tissue (ST) of RA (n=91), PsA (n=15) and OA (n=9) patients using digital image analysis. Immunofluorescence (IF) was used to detect the PRLR expressing cell type. Results: Hyperprolactinemia (PRL-level: 16-24 μg/L) was found in 3.8% of the patients with RA. Prolactin levels were highest in premenopausal compared to postmenopausal females and males. Baseline PRL-levels were significantly lower in responders (median (range): 7.0 (2.0-24) μg/L) than in non-responders (9.3 (4.0-19) μg/L)) on TNF treatment (P=0.009). Higher tertiles of PRL (but within the physiological range) were associated with RF-positivity (P=0.005), aCCP-positivity (P=0.06) and erosive disease (P=0.024). After adjustment for these potential confounders, and for baseline-DAS28, baseline-PRL appeared to be a predictor of non-response to anti-TNF treatment (OR: 4.5; P=0.018; table 1 ). RF and aCCP did not independently contribute. The proportion of patients expressing PRLR in the synovium was similar in RA (66%) and PsA (73%) patients, and lower in OA patients (25%; P=0.05). PRLR expression was higher in RA (median (range): 0.055 (0.000-5.673) IOD/nuclei/mm 2 ) and PsA (0.182 (0.000-5.336)) compared to OA (0.000 (0.000-0.908); P=0.024). Males and (pre-/postmenopausal) females had similar PRLR expression. Using IF, co-localisation was observed with macrophages and endothelial cells. Conclusions: Higher levels of PRL independently predicts a non-response to anti-TNF treatment. The expression of the PRLR in synovial tissue, mainly by macrophages, is higher in the inflammatory diseases (RA and PsA) than in OA. Our combined data suggest an important role of prolactin and its receptor in RA. Disclosure of Interest: None Declared